2018
DOI: 10.1021/acsanm.8b00516
|View full text |Cite
|
Sign up to set email alerts
|

Seeded Growth of Cu2–xSe Nanocrystals and Their Size-Dependent Phototherapeutic Effect

Abstract: Doped semiconductors supporting localized surface plasmon resonances, such as nonstoichiometric copper chalcogenides Cu 2−x Se, have been intensively researched for their potential applications in photoacoustic imaging and photothermal therapy. For these self-doped nanoparticles, their physicochemical attributes such as size and surface chemistry will not only affect their cellular uptake and biodistribution but also influence their own optical properties. Thus, optimization of the physicochemical properties i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…μm −1 at 9399 cm −1 ), 33 the first exciton peak of 5.5 nm PbSe QDs (ϵ abs = 12.7 μm −1 at 6250 cm −1 ), 51 and commercially available infrared dyes (9.8 × 10 4 M −1 cm −1 at 12 690 cm −1 ) 52 all attenuate IR light less efficiently than ITO NCs of minimum 4.5% Sn doping and 12 nm diameter. Alternative extinction coefficient units for these samples are shown in Table S1 for comparison.…”
Section: Nano Lettersmentioning
confidence: 99%
See 2 more Smart Citations
“…μm −1 at 9399 cm −1 ), 33 the first exciton peak of 5.5 nm PbSe QDs (ϵ abs = 12.7 μm −1 at 6250 cm −1 ), 51 and commercially available infrared dyes (9.8 × 10 4 M −1 cm −1 at 12 690 cm −1 ) 52 all attenuate IR light less efficiently than ITO NCs of minimum 4.5% Sn doping and 12 nm diameter. Alternative extinction coefficient units for these samples are shown in Table S1 for comparison.…”
Section: Nano Lettersmentioning
confidence: 99%
“…While several studies have investigated Au NP extinction coefficients, ,,, those of most doped semiconductor NCs, particularly doped metal oxides, are not yet established. Of note, Cu 2– x Se NC dispersions yielded an extinction coefficient of 23.5 μm –1 at 9399 cm –1 for NCs 65 nm in diameter, and recently the extinction coefficient for a film of tin-doped indium oxide (ITO) NCs of 10 atomic% (at%) Sn and 12 nm diameter was reported at 24.3 μm –1 . The applications mentioned above require high extinction coefficient materials to be feasible, and given that doped metal oxide NCs show promise as strong IR absorbers, it is important to quantitatively investigate their optical extinction properties.…”
Section: Quantifying Extinction Coefficients In Nc Dispersionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intracellular ROS level induced by PEG-GNPs (6.2-61.2 nm) was also negatively correlated with NP size in HepG2 and HeLa cells [59]. In addition to GNPs, NPs of other sizes were also negatively correlated with oxidative stress levels in cancer cells, such as silica NPs [60,61], AgNPs [62], PVP-AgNPs [63] and Cu 2-x Se NPs [64].…”
Section: The Impact Of the Nanoparticles' (Np) Physicochemical Propermentioning
confidence: 96%
“…Plasmonic figures of merit such as the extinction coefficient of traditional noble metal NPs can be expressed in terms of the Mie-Gans theory, where their extinction intensities are composed of both absorption and scattering components. Further, for noble metals, it has been widely demonstrated that the plasmonic intensity can be easily manipulated through the scattering cross-section by modulating NP size and/or shape. For example, Jain and El-Sayed’s simulations of plasmonic Au and Ag NPs show tunable extinction coefficients as a function of increasing NP size . It was also demonstrated that the scattering intensities of the plasmonic substrates can be tuned via NP shape anisotropy and/or the formation of hot spots. , To optimize and compare the performance of non-noble metal plasmonic NPs in applications such as surface-enhanced sensing, hot carrier-driven catalysis, and photothermal applications, , it is important to understand and compare the plasmonic extinction tunabilities of semiconductor NPs to those of their noble metal counterparts.…”
Section: Introductionmentioning
confidence: 99%